Demokratične parlamentarne volitve v Srednji in Vzhodni Evropi med letoma 1989 in 1991 in njihov vpliv na oblikovanje strankarskega prostora do leta 2013 - Maver, Aleš (Studia Historica Slovenica, 2018)
The paper's main aim is to describe the changes experienced by party landscapes of the selected former Socialist countries in the Central-East Europe from the period 1989/91 until 2013. The authors try to explain the situation more than two decades later from the historical point of view. All the electoral premieres during the "Spring of nations" from 1989 till 1991 featured a showdown between the ruling Communists and their successor parties and the newly formed or emerging opposition. The opposition was victorious in all the discussed countries other than Bulgaria and Romania. On the other hand, none of the coalitions or big tent parties from the early 1990s survived next two decades. Only in few cases, really stable party systems emerged until 2010s.
Keywords: demokracija; družbene spremembe; politične spremembe; politične stranke; Srednja Evropa; volitve; Vzhodna Evropa